2018
DOI: 10.21577/0103-5053.20180203
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Nerol Derivatives Containing a 1,2,3-Triazole Moiety and Evaluation of Their Activities against Cancer Cell Lines

Abstract: In the present investigation, a collection of twenty two nerol derivatives, containing 1,2,3-triazolic appendages, was synthesized and screened in vitro for their cytotoxic activity against HL60, Nalm6, and Jurkat human leukemia cells as well as against B16F10 (melanoma cell line). In most cases, derivatives were able to reduce cell viability. The most potent compound (Z)-4-(((3,7-dimethylocta-2,6-dien-1-yl)oxy)methyl)-1-(4-(trifluoromethoxy)benzyl)-1H-1,2,3 triazole showed antiproliferative activity against J… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Synthesis of functionalized pyrimidines containing the 1H-1,2,3-triazole ring. 122 Another study involving the use of the Cu(II)/NaAsc catalytic system was reported by Teixeira et al in 2019, 123 in which the authors prepared a series of 1,2,3-triazole compounds from the natural product nerol (Scheme 20). Most compounds showed activity against HL60 human leukemic cells, as well as B16F10 cell lines.…”
Section: Main Sources Of Cu (Ii) Used In Cuaac Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of functionalized pyrimidines containing the 1H-1,2,3-triazole ring. 122 Another study involving the use of the Cu(II)/NaAsc catalytic system was reported by Teixeira et al in 2019, 123 in which the authors prepared a series of 1,2,3-triazole compounds from the natural product nerol (Scheme 20). Most compounds showed activity against HL60 human leukemic cells, as well as B16F10 cell lines.…”
Section: Main Sources Of Cu (Ii) Used In Cuaac Reactionsmentioning
confidence: 99%
“…Synthesis of 1H-1,2,3-triazole derivatives from the natural product Nerol. 123 One of the most positive points of the Cu (II)/NaAsc system is that it is compatible with both oxygen and water, not requiring anhydrous solvents or inert atmosphere. However, Cu(I) residue is cytotoxic and can bind to the active site of many enzymes, blocking or reducing their biological activity.…”
Section: Main Sources Of Cu (Ii) Used In Cuaac Reactionsmentioning
confidence: 99%
“…In this study, a series of twenty-four methoxylated cinnamides containing 1,2,3-triazole fragments were synthesized. Previous investigations conducted by our research group have identified various bioactive compounds containing benzyl groups with different substitution patterns, linked to 1,2,3-triazolyl moieties [ 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. Additionally, the combination of cinnamic acid with benzylated 1,2,3-triazolyl fragments resulted in compounds with significant antileishmanial effect on L. braziliensis [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this study, a series of twenty-four methoxylated cinnamides containing 1,2,3-triazole fragments were synthesized. Previous investigations conducted by our research group have identified various bioactive compounds containing benzyl groups with different substitution patterns, linked to 1,2,3-triazolyl moieties [20][21][22][23][24][25][26]. Addition- Natural products are a valuable resource when exploring therapeutic agents, including for the treatment of leishmaniasis [15].…”
Section: Introductionmentioning
confidence: 99%